(untitled) (The Chittagong University Journal of Science, 2018)
REDD+ implementation and its governance is needed in Bangladesh for resource management, conservation and enrichment of natural forests. REDD+ can generate both carbon and non-carbon benefits to the forest dependent people. On the contrary, good forest governance leads the transparency and accountability in the forest sector. The study was conducted with a view to find out the necessary measures for effective REDD+ implementation in Bangladesh. To realize the objectives, online survey, Focus Group Discussion (FGD) and Key Informants‟ Interview (KII) were used. The study was conducted in Rangamati, Modhupur, and Sreemongal for FGD and KII interviews. For online survey, professional version of „Survey Monkey‟ online software were used. The study found that capacity building for implementation of laws and regulations, strong policy, political influence on right tract, strengthen and empower civil society‟s capacity etc. are the possible resolving measures on REDD+ implementation. Promoting public awareness on laws and regulations, strengthening law enforcement in the forest sector, and successful implementation of policies had been revealed to increase the effectiveness and integrity for the implementation of REDD+ in Bangladesh. The Chittagong Univ. J. Sci. 40(1) : 1-20, 2018